BACTERIOLOGICAL QUALITY OF SOME FERMENTED FOOD PRODUCTS IN KEFFI, NASARAWA STATE (FULafia Journal of Science and Technology, 2016)
Garri, cassava and yam flours are African traditional fermented food products prepared from cassava and yam that is widely accepted by both rural and urban dwelling peoples with little concern about those microorganisms that are associated with it. The present study was undertaken to investigate the bacteria that are associated with these food flours. Total bacterial count (×105 cfu/g) was found to be highest in cassava (7.1), followed by garri (6.2) and yam (4.4). The total coliform count (×105 cfu/g) recorded 3.7 in cassava, 1.6 in garri, and 1.4 in yam flours. Similarly, total faecal coliform (×105 cfu/g) was highest in cassava flour (4.1), while garri had 2.4, and yam recorded 2.2; also, the Staphylococcus aureus count (×105 cfu/g) was highest in cassava flour (3.6),followed by yam flour (3.1), and garri flour had 2.8. However, the Salmonella/Shigella count (×105 cfu/g) was high in garri flour (3.2), compared to cassava flour (2.5), and yam flour (1.2).The percentage occurrence of the bacteria isolates showed that Staphylococcus aureus was 86.7%, followed by Klebsiella spp. (60.0%), Proteus vulgaris (66.7%), E. coli (86.7%).Similarly, percentage occurrence of Salmonella spp. was 80.0% and Bacillus spp. 66.7%. The bacteria isolated were Staphylococcus aureus, Klebsiella spp., Proteus vulgaris, Salmonella spp., E. coli and Bacillus spp. The isolates were further subjected to antibacterial susceptibility tests usingKirby-Bauer disc diffusion method. The antibiotic susceptibility test revealed that most of the bacterial isolates were resistant to Nitrofurantoin (28%), Septrin (36%), Ampicillin (39%), slightly resistant to Perfloxacin (46%), Nalidixic acid (45%), Tetracycline (46%), slightly susceptible to Augmentin (63%), Ciprofloxacin (67%), Ofloxacin (52%) and highly susceptible to Gentamicin (95%). This present work revealed high bioload and vast array of bacteria in market garri, cassava and yam flours. It is therefore recommended that these food flours be sold in well packaged bags and not as exposed in basins/ bowls. Also, personal hygiene of hawkersand sanitation of utensils are important. Hawkers should be enlightened on hygienic practices
Keywords: Bacteriological; quality; garri; cassava; yam flour; Keffi